2022
DOI: 10.3389/fonc.2022.759403
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features, Prognostic Factors and Survival in Patients With Pancreatic Cancer Bone Metastasis

Abstract: PurposeThe purpose of this study is to reveal the clinicopathological features and identify risk factors of prognosis among patients with pancreatic cancer bone metastasis (PCBM).Patients and MethodsPatients with PCBM were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database between 2010 and 2016. Independent predictors for survival of those patients were determined by the univariate and multivariate Cox regression analysis. Forest plots were drawn by GraphPad 8.0.1 and used to visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…As previously reported, the probabilities of peritoneal, liver, lung, bone, and brain metastases from pancreatic cancer were found to be 49.9%, 45.1%, 11.4%, 3.8%, 0.4%, respectively, which indicates that the liver is the most common organ for distant metastasis of PCa (4). Additionally, studies have shown that the prognosis of pancreatic cancer liver metastasis (PCLM) is worse than other distant metastases (5).…”
Section: Introductionmentioning
confidence: 59%
“…As previously reported, the probabilities of peritoneal, liver, lung, bone, and brain metastases from pancreatic cancer were found to be 49.9%, 45.1%, 11.4%, 3.8%, 0.4%, respectively, which indicates that the liver is the most common organ for distant metastasis of PCa (4). Additionally, studies have shown that the prognosis of pancreatic cancer liver metastasis (PCLM) is worse than other distant metastases (5).…”
Section: Introductionmentioning
confidence: 59%
“…In previous reports, lung metastasis was an independent poor prognostic factor for bone metastasis of PC. [13,14] A possible reason for this is that highly malignant bone metastasis had also spread to the lungs because some biomarkers, including IL-6, may be expressed at the same high levels in bone and lung metastases. [17,20] However, PC lung metastasis has been reported to have a better prognosis than liver metastasis or peritoneal dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] However, recent studies including population-based databases, such as the Surveillance, Epidemiology, and End Results database, have gradually clarified the characteristics of bone metastasis in PC. [3,[13][14][15][16] According to these studies, primary tumors of the pancreatic tail, compared to that of the pancreatic head, are more likely to develop bone metastases, [13] and the spine is the most common site of bone metastasis in patients with PC. [16] Based on the above results, in addition to the transarterial metastasis via the circulatory system, transvenous metastasis from the portal vein through the vertebral venous plexus may be involved in the mechanism of bone metastasis from PC.…”
Section: Discussionmentioning
confidence: 99%
“…The early symptoms of PC are insidious and di cult to detect, and many patients have already developed metastases by the time of diagnosis. The incidences of liver, lung, bone, and brain metastasis from PC are 45.1%, 11.4%, 3.8%, and 0.4%, respectively, suggesting that the liver is the most common organ of distant PC metastasis (5). Studies have shown that the organs of metastasis exhibit microscopic changes that favor metastatic growth, known as "pre-metastatic niches (PMNs) ".…”
Section: Introductionmentioning
confidence: 99%